X‐Ray Markers for Thin Film Implants. Issue 18 (7th August 2022) - Woodington, Ben J.; Coles, Lawrence; Rochford, Amy E.; Freeman, Paul; Sawiak, Stephen; O'Neill, Stephen J. K.; Scherman, Oren A.; Barone, Damiano G.; Proctor, Christopher M.; Malliaras, George G.
Abstract: Implantable electronic medical devices are used in functional mapping of the brain before surgery and to deliver neuromodulation for the treatment of neurological and neuropsychiatric disorders. Their electrode arrays are assembled by hand, and this leads to bulky form factors with limited flexibility and low electrode counts. Thin film implants, made using microfabrication techniques, are emerging as an attractive alternative, as they offer dramatically improved conformability and enable high density recording and stimulation. A major limitation of these devices, however, is that they are invisible to fluoroscopy, the most common method used to monitor the insertion of implantable electrodes. Here, the development of mechanically flexible X‐ray markers using bismuth‐ and barium‐infused elastomers is reported. Their X‐ray attenuation properties in human cadavers are explored and it is shown that they are biocompatible in cell cultures. It is further shown that they do not distort magnetic resonance imaging images and their integration with thin film implants is demonstrated. This work removes a key barrier for the adoption of thin film implants in brain mapping and in neuromodulation. Abstract : The development of flexible X‐ray markers using bismuth and barium‐infused elastomers and their integration with thin‐film bioelectronic implants is presented. This work removes a key barrier for the adoption of thin film implants in brain mapping and in neuromodulation.